A pedagogic compact: retrieving 'powerful' educational knowledge from Didaktik and curriculum studies. Issue 2 (4th March 2021) - Muller, Johan; Hoadley, Ursula
ABSTRACT: We set out to address the question—what does it mean for educational knowledge to be 'powerful'? We compare the Anglo tradition of curriculum studies with the Didaktik tradition through the lens of an analysis of curriculum structure in postgraduate courses in South African universities rooted in either the Anglo or Didaktik tradition. This analysis of curriculum structure affords a view of each tradition that we argue is 'powerful', but in different ways. While Didaktik provides a humanities-based curriculum coherence in teacher education, curriculum studies offers social scientific possibilities for empirical inquiry. We make the argument that a strategic entente cordiale, or pedagogic compact, would strengthen the professional position of teachers and education academics in the respective countries. This is particularly so in the context of threats posed by instrumental trends driven by educational sciences underpinning TIMSS, Pisa and the like.